Evaluation on the pore and water-permeability of woven conical tubular vascular graft with continuous variable cross sections. Issue 8 (3rd August 2021) - Meng, Fen-Ye; Li, Yu-Ling; Ma, Yan-Xue
Abstract: Considering the wall smoothness and mechanical continuity of conical tubular vascular grafts, the conical tubular vascular graft with continuous variable cross-sections (CVC) has been successfully woven on the basis of the equal-cover-factor principle. However, the tubular wall property and its effect on water permeability is still unknown, which is one of the fundamental properties for woven vascular grafts. In this study, a series of CVC conical tubular prototypes with different conical degrees and typical fabric weaves were prepared, and their wall features and the water permeability along the tubular walls were measured. And then, the study investigated the uniformity of the wall structure as well as the relationship among water permeability, and porosity and pore sizes. The results show that these samples have statistically uniform pore features and water permeability along the graft wall, but both the pore features and the permeability are sensitive to the conical degree as well as fabric weaves. Moreover, the water permeability has a significant parabolic relationship with the pore size, while there is no significant dependence on the porosity. These results demonstrate advantages of the CVC tubular vascular graft produced in the equal-cover-factor principle, and will facilitate the development of the CVC woven tubular vascular graft.